Minerals in the Blood, Hair, and Faeces of the Critically Endangered Western Derby Eland Under Human Care in Two Wildlife Reserves in Senegal - Stoklasová, Lucie; Váhala, Jiří; Hejcmanová, Pavla (Biological trace element research, 2020)
The widely used means of investigating animal mineral profiles are blood serum or plasma and internal organ tissues. The acquisition of these types of samples can be invasive and requires much effort. These factors become key obstacles in the case of rare and elusive species such as the Western Derby eland (Taurotragus derbianus derbianus, WDE), which is a critically endangered antelope with a current distribution limited to the Niokolo Koba National Park, and two wildlife reserves in Senegal. One of the solutions to this problem is to collect easily accessible samples, such as faeces or fur, which may provide valid information about animal mineral status. Our study focuses on determining the macroelement and microelement levels in animal blood serum, hair, and faeces, and analysing their correlations to evaluate whether hair and/or faeces can be used as a proxy for blood mineral levels. Samples were collected from 11 individual WDEs (6 males, 5 females) during translocations within two reserves. Correlations of mineral concentrations in the blood, hair, and faeces were not found except for Fe in the faeces, which was positively correlated with Fe in the hair (r = 0.64, P < 0.05) and blood (r = 0.69, P < 0.05). The lack of correlations among the different types of samples may be because of the low number of samples; hence, we recommend conducting further research with a broader dataset. Our findings, however, currently indicate that faeces and fur analyses cannot stand alone for the assessment of the mineral status and the determination of WDEs' potential mineral deficiencies.
Keywords: Mineral profile; Conservation translocation; divoká zvířata; feces; Humans; vlasy, chlupy; Female; Giant eland; Wildlife nutrition; lidé; zvířata; Large antelope; Animals, Wild; Feces; Minerals; Hair; ženské pohlaví; Male; Senegal; Animals; West Africa; mužské pohlaví; minerály